Daang hari - Saez, Nilo.; Lea Production (Firm). ([s.l.] Lea Production)
Don Manolo is very much obsessed w/ the crown and scepter as well as w/ the Cristo Rey to be part of his collection. He would pay no matter how much it would cost. He does not care on how are they going to get it for him. The first set was the crown and scepter and the second set was the Cristo Rey icon including the life of Mang Simon, the father of Gabriel who was sacrificed because he is the leader of their barrio taking care of church treasures. Gabriel, a former guerrilla who just came back from Word War II would move heaven and earth to get all the church treasures back again to its home church not only to continue the mission of his father but also to end the greediness of people like Major Gonzalo and Buwitre.
VCD
Story of Carlo J. Caparas, screenplay by Jose Carreon, executive producer Emilia Santos-Blas, directed by Nilo Saez
Fernando Poe, Jr., Lani Mercado, Eddie Garcia
Keywords: Feature films; Action films